Modeling biophysical and biological properties from the characteristics of the molecular electron density, electron localization and delocalization matrices, and the electrostatic potential - Matta, Chérif F (Journal of computational chemistry, 2014)
Copyright © 2014 The Authors Journal of Computational Chemistry Published by Wiley Periodicals, Inc.